A Review of Postgraduate Theses on "Teaching History" - Şengül Bircan, Tuba (Atlas Journal, 2024)
The study aims to reveal the status of recent studies by examining the title and abstract sections of postgraduate theses prepared on history teaching. The sample of the study consists of postgraduate theses prepared in Turkey between 2020-2024 and accessible by scanning the "National Thesis Center" database. The keywords "history teaching" and "history education" were used during the scanning. 28 postgraduate theses that met these criteria were scanned. In the study, which was conducted with the systematic scanning design of the qualitative research method, the "Thesis Scanning Form" developed by the researcher was used as a data collection tool. Descriptive analysis was applied in the analysis of the study data. As a result of the research, deficiencies in thesis abstract writing were identified, and postgraduate theses prepared on history teaching were classified into 11 categories. It was observed that the theses concentrated on the categories of history teaching in innovative environments, views on history teaching practices, and literature review.